PREGNANCY RISKS IN ADVANCED MATERNAL AGE: A CASE REPORT - I Nyoman Adi Wacika (Yayasan Pendidikan Medika Indonesia, 2025)
Advanced maternal age pregnancy refers to pregnancies occurring in women over the age of 35. Complications during pregnancy are a significant cause of maternal mortality, with maternal age being one of the risk factors. In 2021, the birth rate among women aged 35-39 was 54.2 births per 1,000 women, while for those aged 40-44, it was 12.1 births per 1,000 women. This case report highlights the risks associated with advanced maternal age pregnancy, making it an interesting topic for discussion. The aim of this study is to summarize the history, physical findings, laboratory results, and pregnancy risks associated with advanced maternal age. This is a case report of a 44-year-old multiparous woman who was referred to Dr. Abdoer Rahem General Hospital with hypertension and hyperglycemia since the seventh month of pregnancy. She was diagnosed with a third-degree obstetric anal sphincter injury, preeclampsia with HELLP syndrome, and gestational diabetes. Physical findings included a blood pressure of 197/107 mmHg, a laceration in the perineal region with situational suturing, decreased anal sphincter tone, and a positive pill-rolling test. Laboratory results showed Hb 11.2 g/dL, PLT 39,000, AST 353, ALT 153, HbA1c 7.4, and a random glucose test of 276mg/dL. The risks of pregnancy in advanced maternal age include preeclampsia, gestational diabetes, and perineal lacerations.